Efek Pemberian Ekstrak Biji dan Ekstrak Daun Pepaya (Carica papaya Linn) terhadap Kadar Kolesterol Total dan Trigliserida Tikus Putuh Jantan Galur Wistar (Rattus norvegicus) yang Diberi Diet Tinggi Lemak - Esa Putri Ridha Yanti (HANG TUAH MEDICAL JOURNAL, 2017)
Background. In Indonesia the incidence of cardiovascular diseases has been increasing from year to year and one of the risk factors are hyperlipidemia, especially hypercholesterolemia. Studies suggest that the content of papaya seeds that could potentially cause hypocholesterolemic effects are flavonoids, saponins and tannins. In the phytochemical screening for papaya leaves indicate the presence of alkaloids, flavonoids, tannins, and glucosidal. This study aims to determine the effect of papaya seed extract and papaya leave extract on levels of total cholesterol and triglycerides in white male rat (Rattus norvegicus) wistar strain which administrated with high fat diet. Methods. This test is using Post Test Only Control Group Design with simple random sampling technique. Sample uses 32 white male Rattus norvegicus Wistar strain those further divide into 4 groups: negative control group, a group of experimental animals were given a high-fat diet, a group of experimental animals were given a high-fat diet and aqueous papaya seeds extract and a group of experimental animals were given a high-fat diet and aqueous papaya seeds extract. This test had done in Biochemical Laboratory of Hang Tuah University. Results. The results analysis using Kruskal-Wallis and One Way Anova test showed minor decrease of triglyceride and total cholesterol in a group of experimental animals were given high-fat diet and aqueous papaya seeds extract, and a group of experimental animals were given high-fat diet and aqueous papaya leaves extract (p >0,05). Conclusion. Aqueous papaya seeds extract and aqueous papaya leaves extract does not decrease level of total cholesterol and triglycerides.